2009
DOI: 10.1158/0008-5472.sabcs-09-4156
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Androgen Receptor in Breast Cancer.

Abstract: Background: Androgen receptor (AR) is one of biomarkers and its role in breast cancer is still unclear. The aim of this study was to investigate the relationship between AR expression and clinicopathological factors in breast cancer patients.Patients and Methods: AR was consecutively evaluated in 413 primary breast cancers from whole sections of surgically resected specimens using immunohistochemical staining from January 2008 to March 2009. The associations between AR expression and clinicopathological parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[10][11][12] About 25% to 75% of TNBCs show androgen receptor (AR) expression; many, but not all, of these tumors are apocrine carcinomas. [13][14][15][16][17] It is this latter group (AR þ TNBCs) that is of special interest in this review for a potential benefit from AR-targeted therapies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] About 25% to 75% of TNBCs show androgen receptor (AR) expression; many, but not all, of these tumors are apocrine carcinomas. [13][14][15][16][17] It is this latter group (AR þ TNBCs) that is of special interest in this review for a potential benefit from AR-targeted therapies.…”
mentioning
confidence: 99%
“…59,60 Moinfar et al 61 found AR expression in 90% of grade 1 invasive breast cancers compared with 47% of grade 3 invasive breast carcinomas and concluded that AR is the most frequently expressed marker even among high-grade breast carcinomas. Although the reported expression rate for AR has varied widely-probably because of different cutoff points [13][14][15][16][17]59,62 used in various studies-it has been suggested that its expression in TNBC has prognostic value. 57,60,62,63 Using the 1% criterion for ER, PR, and AR positivity, along with a 30% threshold for HER2 immunohistochemical evaluation, a recent study of 325 invasive breast cancers found 21 cases (6.5%) that were only AR positive and 33 that were AR and HER2 positive.…”
mentioning
confidence: 99%
“…Interestingly, these genes are commonly mutated in cancer patients, and the loss of their function often results in a more aggressive cancer phenotype. Although not acting mechanistically as a TF, BRCA1-2 directly influence TFs, such as AR [5] and MYC [6]. Given their importance, the discussion surrounding their roles in cancer and their potential as therapy targets is a topic of significant debate [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%